WHEN MEMORY BECOMES DEBRIS: AESTHETIC MODES OF REPRESENTING DISASTER LOSS (University of Bucharest Review. Literary and Cultural Studies Series, 2024)
The concept of public forgetting by Bradford Vivian explains how acts of forgetting are utilized to enhance selective and normative public remembrance. One common example is when tons of debris caused by a natural disaster that once functioned as material memory either on a personal or collective levels were taken away. How do people respond to this kind of loss when such memory has to be disposed of as waste? Japanese disaster memory discourse aims to disseminate knowledge of disaster prevention, preparedness, and commemoration of victims, while the ways disaster survivors make sense of their losses individually have yet to be examined. The Kobe City’s monument and the annual commemorative service of the 1995 Great Hanshin-Awaji earthquake bring about chronological post-disaster temporality among the general public. However, three different survivor testimonies this article analyzes show that individual kins of the deceased called izoku continue to nurture their memories of the deceased relevant to their current lives; their memories are related to the past trauma, but they are simultaneously interrelated memories in the present. James E. Young’s concept of texture of memory, Giuliana Bruno’s concept of fabrics of the visual, and Ernst van Alphen’s concept of reintegration of subjectivity and body are examined to consider the way a survivor/izoku connects lost material memory with the present living memory. The series of earthenware works crafted by a survivor/izoku are analyzed to consider how she makes sense of absence and presence of the deceased in her present everyday life. The author proposes decomposed memory as a concept of processing memory as debris, where memory needs to be appropriately decomposed and transformed by individuals into interrelated memory.